2021
DOI: 10.3389/fpubh.2021.758030
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Knowledge About SARS-CoV-2 & COVID-19 Among University Students Are Associated With Negative Attitudes Toward People With COVID-19: A Cross-Sectional Study in Cyprus

Abstract: University students represent a highly active group in terms of their social activity in the community and in the propagation of information on social media. We aimed to map the knowledge, attitudes, and perceptions of University students in Cyprus about severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and Coronavirus disease 2019 (COVID-19) to guide targeted future measures and information campaigns. We used a cross-sectional online survey targeting all students in conventional, not distance-learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…At the time this research was initiated, there were very few reports of attitudes towards prevention among students, which is a notable gap as student perceptions and adherence to prevention guidelines may vary substantial from other groups. However, since the start of the COVID-19 pandemic, research has explored the rate of students’ compliance with preventive measures [ 23 26 ] as well as attitudes or perceptions towards preventive measures among Iranian high school students [ 27 ] or among university students from the Middle East [ 28 , 29 ], Asia [ 30 , 31 ], Europe [ 32 , 33 ], and black college students from North Carolina, USA [ 34 ]. Therefore, the purpose of this study is to add to this growing body of literature to explore the perceptions and awareness of COVID-19 prevention measures among students at a large United States university.…”
Section: Introductionmentioning
confidence: 99%
“…At the time this research was initiated, there were very few reports of attitudes towards prevention among students, which is a notable gap as student perceptions and adherence to prevention guidelines may vary substantial from other groups. However, since the start of the COVID-19 pandemic, research has explored the rate of students’ compliance with preventive measures [ 23 26 ] as well as attitudes or perceptions towards preventive measures among Iranian high school students [ 27 ] or among university students from the Middle East [ 28 , 29 ], Asia [ 30 , 31 ], Europe [ 32 , 33 ], and black college students from North Carolina, USA [ 34 ]. Therefore, the purpose of this study is to add to this growing body of literature to explore the perceptions and awareness of COVID-19 prevention measures among students at a large United States university.…”
Section: Introductionmentioning
confidence: 99%
“…Experiences in this regard have shown that taking preventive measures in order to control the disease requires social awareness from all people, and one of the most important measures is to determine the level of knowledge, attitude, and self-care behavior and improve these components [9][10][11][12]. The results of some studies have shown that a high level of knowledge about a disease is directly related to self-care behaviors [13][14][15][16], and some other studies have shown that a high level of attitude can predict these behaviors [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%